Novel Approaches for Encapsulation of Plant Probiotic Bacteria with Sustainable Polymer Gums: Application in the Management of Pests and Diseases - Roohallah Saberi Riseh; Elahe Tamanadar; Mojde Moradi Pour; Vijay Kumar Thakur (Advances in Polymer Technology)
The unique attributes, biodegradability, biocompatibility, perfect accessibility, and low production costs led to the use of natural gums in a different section of our lives. Among them, we can mention gums obtained from microorganisms (xanthan gum and gellan gum), plant tissues (Arabic gum and gum tragacanth), seeds (konjac gum and guar gum), seaweeds (alginates, agar gum, and carrageenans). Gums have essential applications in the medical and pharmaceutical, food, biotechnology, and critical agricultural industries. Encapsulation is one of the new methods to increase the stability of bioactive compounds during processing and storage. Encapsulation technology using natural gums is a new way to improve the performance of microbial agents in various sciences, especially agriculture, which represents a bright future in this field.